Interplay between singlet and triplet excited states in a conformationally locked donor–acceptor dyad. Issue 44 (21st October 2015) - Filatov, Mikhail A.; Etzold, Fabian; Gehrig, Dominik; Laquai, Frédéric; Busko, Dmitri; Landfester, Katharina; Baluschev, Stanislav
Abstract : The synthesis and photophysical characterization of a palladium(ii ) porphyrin – anthracene dyad bridged via short and conformationally rigid bicyclo[2.2.2]octadiene spacer were achieved. Abstract : The synthesis and photophysical characterization of a palladium(ii ) porphyrin – anthracene dyad bridged via short and conformationally rigid bicyclo[2.2.2]octadiene spacer were achieved. A spectroscopic investigation of the prepared molecule in solution has been undertaken to study electronic energy transfer in excited singlet and triplet states between the anthracene and porphyrin units. By using steady-state and time-resolved photoluminescence spectroscopy it was shown that excitation of the singlet excited state of the anthracene leads to energy transfer to the lower-lying singlet state of porphyrin. Alternatively, excitation of the porphyrin followed by intersystem crossing to the triplet state leads to very fast energy transfer to the triplet state of anthracene. The rate of this energy transfer has been determined by transient absorption spectroscopy. Comparative studies of the dynamics of triplet excited states of the dyad and reference palladium octaethylporphyrin (PdOEP) have been performed.